Comparative Studies Simulation Software for Bone Plate Compression - Mayasari, Dita; Muhammad, Sirojuddin Kholil; Triwardono, Joko; Malau, Daniel Panghihutan; Utomo, Muhammad Satrio; Asmaria, Talitha (Metalurgi, 2023)
Medical applications occasionally require PSI (patient-specific implant) designs to match the implant bone’s geometry. To verify and predict failures of the design as well as a treatment before the manufacturing process, FEA (finite element analysis) is employed to simulate when given a specific number of loads. Plenty of studies have done the FEA using a couple of types of software; however, to the best of our knowledge, there is no literature to compare those several FEA results with a comparable experiment. This study further analyzes material stress, particularly to compute the VMS (Von Misses stress) of the Ti6Al4V bone plate. Furthermore, this study proposes to examine and deliver a comprehensive understanding using the four most used software of COMSOL, Ansys, Abaqus, and Autodesk Inventor. The results of those four simulations are then compared with the stress test through the Hardness Vickers test. This study will contribute significantly as a novel comparison between VMS and hardness test as a stress prediction in an implant material.